Very Early Presentation of Extrahepatic Portal Vein Obstruction Causing Portal Hypertension in an Infant: Uncertainties in the Management and Therapeutic Limitations - Khodayar-Pardo, Parisá (Case Rep Gastroenterol, 2016)
Extrahepatic portal vein obstruction, although rare in children, is a significant cause of portal hypertension (PHT) leading to life-threatening gastrointestinal bleeding in the pediatric age group. PHT may also lead to other complications such as hyperesplenism, cholangyopathy, ascites, and even hepatopulmonary syndrome and portopulmonary hypertension that may require organ transplantation. Herein we report the case of an asymptomatic 11-month-old infant wherein a hepatomegaly and cavernous transformation of the portal vein was detected by liver ultrasound. Neither signs of thrombosis in arteriovenous system, nor affectation of biliary tract were identified in the magnetic resonance imaging study. A significant enlargement of the caudate lobe of the liver was reported. No risk factors were detected. The differential diagnosis performed was extensive. Inherited thrombophilia and storage disorders were especially considered. Liver biopsy was normal. Upper gastrointestinal esophagogastroduodenoscopy detected two small varicose cords on the distal third of the esophagus. Finding a cavernous transformation of the portal vein with evidence of collateral circulation in such an early age is a challenging condition for professionals, since PHT may lead to severe complications during childhood and can compromise growth and development. Evidence-based guidelines for the management of PHT in adults have been published. However, follow-up and treatment of pediatric patients have not yet been standardized. Moreover, management of PHT in infants faces particular difficulties such as technical restrictions that could hinder their treatment.